METHODS OF APPLYING PEDAGOGICAL AND INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Jahongir Sobirovich Botirov; Nodira Yuldasheva (Scholar Express Journal, 2021)
One of the main elements of the educational work carried out in the classroom is the fact that students perform independent, free-thinking learning and practical tasks on the basis of interaction, which, of course, leads to maturity in life. Any interactive methods used in the lessons are educational in nature and help to consolidate, define and expand students ’knowledge, generalize and systematize them.
Keywords: Lesson; education; upbringing; student